2022
DOI: 10.1097/ta.0000000000003598
|View full text |Cite
|
Sign up to set email alerts
|

Do not forget the platelets: The independent impact of red blood cell to platelet ratio on mortality in massively transfused trauma patients

Abstract: In this nationwide analysis of massively transfused trauma patients, unbalanced PLT transfusion was more prevalent than unbalanced FFP. The impact of unbalanced PLT transfusion on 24-hour mortality was independent from and potentially more pronounced than unbalanced FFP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 49 publications
0
12
0
1
Order By: Relevance
“…The effect of higher platelet doses as well as empiric platelet transfusion in trauma patients without thrombocytopenia as part of a balanced transfusion strategy with other blood products is controversial. Data from French [ 262 ] and US [ 312 ] trauma registries support platelet transfusion despite a normal platelet count [ 262 ] and maintenance of a platelet/pRBC ratio closer to1:1, respectively. Recent systematic reviews also found that higher platelet/pRBC ratios result in a significant decrease in short-term (24 h) and long-term (28–30 day) mortalities [ 313 , 314 ], lower ICU length of stay (LOS) and higher ICU-free days [ 314 ], without influencing the occurrence of thromboembolic events or organ failure [ 313 ] when compared with lower platelet/pRBC ratios.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of higher platelet doses as well as empiric platelet transfusion in trauma patients without thrombocytopenia as part of a balanced transfusion strategy with other blood products is controversial. Data from French [ 262 ] and US [ 312 ] trauma registries support platelet transfusion despite a normal platelet count [ 262 ] and maintenance of a platelet/pRBC ratio closer to1:1, respectively. Recent systematic reviews also found that higher platelet/pRBC ratios result in a significant decrease in short-term (24 h) and long-term (28–30 day) mortalities [ 313 , 314 ], lower ICU length of stay (LOS) and higher ICU-free days [ 314 ], without influencing the occurrence of thromboembolic events or organ failure [ 313 ] when compared with lower platelet/pRBC ratios.…”
Section: Resultsmentioning
confidence: 99%
“…Platelets are important in the treatment of bleeding but are often not available or of insufficient supply in many rural hospitals in our country as well as other countries and thus bleeding patients may not be optimally treated (2,21). Initially, we included patients in two remote hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, many smaller hospitals have no platelets stored locally, leading to several hours of delay before treatment. In treatment guidelines for bleeding, the early use of blood products is recommended and has improved survival (2,3). Platelets are crucial for hemostasis in bleeding patients (4) resulting in reduced use of red blood cells and plasma products, which is important in hospitals with limited blood inventory (5).…”
Section: Introductionmentioning
confidence: 99%
“…The three exposure groups will be defined as receipt of (1) only WFWB, (2) only LTOWB, and (3) both WFWB and LTOWB compared with the receipt of a 1:1:1 balanced ratio of plasma/platelets/RBCs (nonexposure). Balanced component transfusion will be defined as RBC/plasma ≤2 and RBC/platelet ≤2 22,23 …”
Section: Methodsmentioning
confidence: 99%